Healthy Eating: Drink to Your Health - Jennifer Hillan; Emily Minton (EDIS)
Shakes and smoothies are a great and tasty way to incorporate more fruits and nutrients into your diet. This 2-page fact sheet was written by Jennifer Hillan and Emily Minton, and published by the UF Department of Family, Youth and Community Sciences, March 2012.